Deformation mechanism and cyclic stress response of Zircaloy-4 alloy cladding tube during low cycle fatigue at room temperature. (July 2022) - Guo, Wenbin; Li, Geping; Han, Fuzhou; Zhang, Yingdong; Ali, Muhammad; Ren, Jie; Wang, Qichen; Yuan, Fusen; Tong, Min
Highlights: Strain amplitude dependence of cyclic softening and hardening behavior is investigated. Microstructure evolution, e.g. grain rotation and twinning, depends strongly on the proportion of plastic and elastic strain amplitude. The relationship between cyclic stress response and deformation modes is understood. Abstract: This work systematically investigated the deformation mechanism and cyclic stress response behavior of Zircaloy-4 alloy cladding tube at room temperature. Low cyclic fatigue tests revealed that cyclic softening and hardening strongly depend on the applied strain amplitude. Besides, prismatic < a > slip was the primary cyclic deformation mode when the value of plastic strain amplitude less than that of elastic strain amplitude, otherwise prismatic < a > slip and { 10 1 ¯ 2 } < 1 ¯ 011  > twinning dominated the deformation. Due to the combination effect of grain rotation, dislocation accumulation and twinning, cyclic softening, saturation and hardening behaviors were presented in Zircaloy-4 alloy.